(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
My paper provides a brief summary of the early history of Hungarian kindergarten teacher training. It outlines the developmental process which began with the foundation of the first kindergarten teaching institute (Tolna, 1837) and ended with the opening of the three tertiary level training institutions in 1959. It introduces and briefly characterises the main stages of the progress especially focusing on the tendencies and plans directed by the special nature of national kindergarten teacher training in higher education.